Optical properties of thin Bi2Te3 films synthesized by different techniques. (July 2021) - Adam, A.M.; Tolan, Mohamed; Refaat, A.A.; Nafady, Ayman; Petkov, P.; Ataalla, M.
Abstract: Thin films of Bi2 Te3 alloy were grown by vacuum thermal evaporation (VTE) and pulsed laser deposition (PLD) techniques. The growth was conducted on clean substrates of non-conductive glass. X-ray diffraction (XRD) analysis was used to study the materials crystal structure. The XRD patterns revealed the crystalline nature of the prepared films. Surface morphology was investigated by the atomic force microscopy (AFM) showing that the films are formed of crystallites bounded by twin boundaries oriented in the c-axis in a way that perpendicular to the substrate plane. The samples shown to be stoichiometric and of good morphology. Transmission and reflection spectral have been obtained at room temperature using a double beam Jasco spectrophotometer. Absorption coefficient, extinction coefficient and refractive index were determined. The optical band gap was evaluated by measuring the fundamental absorption and extrapolation of the linear portion of (αhν) 2 versus hν plots. The plots indicated direct allowed transition. Comparison between all optical parameters of the films prepared by the two different methods has been performed. Highlights: Thin Bi2 Te3 films were grown by two different techniques. Structure and morphology were investigated. Optical properties of the films were studied and compared. Direct allowed band transition is revealed in both films.